Puebloan Societies : Homology and Heterogeneity in Time and Space - Whiteley, Peter M. (Book collections on Project MUSE., 2018)
"Pueblo sociocultural formations of the past and present are the subject of the essays collected here. The contributors draw upon the insights of archaeology, ethnology, and linguistic anthropology to examine social history and practice, including kinship groups, ritual sodalities, architectural forms, economic exchange, environmental adaptation, and political order, as well as their patterns of transmission over time and space. The result is a window upon how major Pueblo societies came to be and how they have changed over time. As an interdisciplinary conjunction, Puebloan Societies demonstrates the value of reengagement among anthropological subfields too often isolated from one another. The volume is an analytical whole greater than the sum of its parts: a new synthesis in this fascinating region of human cultural history"--